NEEDS FOR LOVE AND BELONGINGNESS OF SINGLE PARENT IN MARK ROSMAN'S THE PERFECT MAN MOVIE: HUMANISTIC PSYCHOLOGICAL APPROACH - RAMADHANI, INTAN RIZQI (2010)
The major problem of this research paper is how needs for love and belongingness is portrayed in Jean feeling as a single parent which influences her to looking for the perfect man to be her husband in The Perfect Man movie based on Humanistic Psychological Analysis. Thus, here the research analysis is focused on Jean Hamilton as the major character. In this research, the writer employs the qualitative method. In this method, the researcher uses two data sources which namely primary data and secondary data sources. The primary data source is The Perfect Man movie, the secondary data source are the books about Psychological, some books about Humanistic, and another virtual references. Next, the other sources which are related to this analysis. The method of data collection is literary research and the technique of data collection is descriptive technique. Based on the analysis, the outcome of this study demonstrates the result of following conclusion. Firstly, the structural elements the movie presents a form of unity which included in narrative element and technical element. It appears in beginning, middle and the end of the story. Secondly, the research shows that The Perfect Man movie illustrates about single parent's love relationship and describes how love and belonging need reflect on the major characters personalities. Finally, the psychological analysis shows that people will do everything to achieve their goal. Mark Rosman describes the level of Jean's needs which are evaluated in Humanistic Psychological approach. The major character, Jean can complete the five basic needs easily, especially in the third basic level.